(3GfMQGa GdSdWI GdJCSjSjI (B: s (3OQGSI ebGQfI (B/ s - (3Cjef YjO GdSjO GdSYOfis; (3UHQi eMeO GdSfhSi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2020)
(3JfGhdJ GdOQGSI ehVhY (B"(3GfMQGa GdSdWI GdJCSjSjI(B": (3h bO LGAJ aj ebOeI(B: (3h aUd JegjOi(B: (3h KdGKI CHhGH(B: (3h NGJeI(B. (3h HjfJ GdOQGSI cja GfJbdJ acQI GdGfMQGa ef GdbGfhf GdeOfi Edi GdbGfhf GdEOGQi Ke Edi GdbGfhf GdOSJhQi(B: (3h CcOJ EecGfjI hbhY GdGfMQGa ef GdSdWI GdJCSjSjI(B: (3ShGA ef GdSdWI GdJCSjSjI GdCUdjI CKfGA hVY GdOSJhQ Ce ef GdSdWI GdJCSjSjI GdefnTCI CKfGA JYOjdg(B. (3h deG cGf GdGfMQGa dG jchf abW ai Yed gPg GdSdWI YfO hVY GdhKjbI Ch JYOjdgG(B: (3h EfeG bO jchf cPdc ai WQjbI JTcjdgG` cGf dRGkeG Cf JJfGhd GdOQGSI WQb hVY GdOSGJjQ h CKQ cd WQjbI efgG Ydi GdGfMQGa GdPi bO jdMb HGdhKjbI GdOSJhQjI(B: (3h bGeJ HGdJWHjb Ydi GdLeYjGJ GdJCSjSjI GdJi hVYJ GdOSGJjQ GdeUQjI(B. (3Ke HYO Pdc JfGhdJ GdOQGSI eNJda GdhKGFb GdOSJhQjI ai eUQ; HHjGf GdfUhU GdJi JKjQ THgI GfMQGa GdSdWI GdJCSjSjI(B. (3Ke JfGhdJ SdWI JYOjd GdOSJhQ h GdbjhO GdJi JQO Ydi YedgG(B: (3h CfgG Ef NGdaJ gPg GdbjhO Jchf bO GfMQaJ HSdWJgG(B. (3h CcOJ GdOQGSI CNjkQG Ydi Cf GdGSJaJGA GdOSJhQi dG jecf Cf ojWpqgQ GdfUhU GdefMQaI ef GdYjhH(B. (3h NdUJ GdOQGSI Edi Cf GdOSGJjQ dG jfHZi Cf oJcnJH abW JYHjkQG Yf CacGQ SGejI eLQOI Yf GdMQjI h GdOjebQGWjI h Mbhb GdEfSGf(B: (3Ohf Cf JYHQ Yf hGbY GdehGWfjf GdSjGSi h GdGLJeGYi h GdGbJUGOi(B: (3MJi dG JfaUd GdhKjbI GdOSJhQjI Yf hGbY GdMjGI(B: (3ajdLC GdTYH Edi JZjjQgG HGdWQb ZjQ GdbGfhfjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2020s
(3HHdjhLQGajG(B: (3UaMGJ (B337-347s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3JYOjd GdOSJhQs; (3GdLeYjI GdJCSjSjIs; (3OSJhQs; (3GdSdWI GdJCSjSjIs; (3GdGSJaJGA GdOSJhQjs; (3GdGSJaJGA GdSjGSjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes